Analisis Vitamin C Pada Loloh Cemcem (Spondias Pinnata) Menggunakan Daun Stevia (Stevia Rebaudiana B.) Dengan Metode Spektrofotometri Uv-Vis - Pande P. Elza Fitriani; Anak Agung Ngurah Dwi Ariesta Wijaya Putra; Ida Ayu Putu Ary Widnyani (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2021)
Vitamin C is one of the essential vitamins for humans that cannot be produced by the body itself. One of the fulfillments of vitamin C can be obtained through local nutraceutical, namely loloh cemcem. Loloh cemcem is one of healthy Balinese authentic beverage originating from Penglipuran Village, Bangli. Loloh cemcem is herb beverage made from forest ambarella leaves that are widely grown in Bangli. This study aimed to analyze the content of vitamin C in loloh cemcem with stevia leaves by UV-Vis Spectrophotometry Method. This study was a randomized complete design 1 factorial with 5 treatments of stevia leaves concentration and repeated 3 times. The results of the study on samples with stevia concentration of 5%, 7%, 9%, 11% and 13%, were 2.26%, 2.16%, 2.11%, 1.85% and 1.76% of vitamin C, respectively. This indicated that the more stevia concentrations given, the lower of vitamin C content could be produced. This product can be one of the options in the fulfillment of vitamin C for diabetics or those who limit their daily sugar intake to meet daily vitamin C needs.